Decreased work productivity due to primary palmar hyperhidrosis. What is the cost?. Issue 2 (5th April 2021) - Kristensen, J. K.; Nielsen, C.
Abstract : A decrease of 7, 2 % in productivity was found in patients suffering from palmar hyperhidrosis. A correction of this could more than pay for the treatment with botulinum‐toxins, even 3 or 4 times a year.